Mullite porous ceramic and preparation method thereof

By using raw materials and additives such as fly ash, aluminum-containing compounds, malosite, kaolin and titanium-containing compounds, combined with specific preparation processes, the problems of high sintering shrinkage and uneven pore size distribution when preparing mullite porous ceramics are solved, and the preparation of mullite porous ceramics with low sintering shrinkage, high porosity and excellent mechanical strength is achieved, simplifying the process and reducing costs.

CN119912271APending Publication Date: 2025-05-02北京钢研新冶工程技术中心有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510179407.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The prior art is difficult to effectively use fly ash to prepare mullite porous ceramics with low sintering shrinkage and uniform pore size distribution, and the process is complicated.

Method used

Fly ash is used as the silicon source, aluminum-containing compounds are used as the aluminum source, and rutile is used as the sintering regulator. Combining kaolin and titanium-containing compounds are used as additives, the near-net size preparation of mullite porous ceramics is achieved through a specific preparation process.

Benefits of technology

The low sintering shrinkage rate (≤1%), high opening porosity (≥40%), uniform pore size distribution and excellent mechanical strength of mullite porous ceramics are achieved, which simplifies the production process and reduces the cost of raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912271A_ABST
    Figure CN119912271A_ABST
Patent Text Reader

Abstract

According to the mullite porous ceramic and the preparation method thereof provided by the invention, solid waste fly ash is used as a raw material, andalusite is introduced as a silicon source regulator, alumina or calcined alumina is used as an aluminum source, and proportioning is carried out according to the chemical composition of near mullite; meanwhile, the structure of the mullite ceramic is regulated and controlled by combining the particle size of the raw material, a compression molding process and segmented sintering preparation. In the process, the preparation of the near-net-size mullite porous ceramic can be effectively realized through particle accumulation and volume expansion accompanied by mullite generation in the sintering process, the sintering shrinkage rate is less than or equal to 1%, the open porosity is more than or equal to 40%, the pore size distribution is unimodal distribution, and the bending strength is gt; and meanwhile, good gas flux is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a mullite porous ceramic and a production method thereof, in particular to a method for preparing the mullite porous ceramic by using solid waste fly ash as a main raw material and combining a specific sintering control technology. Background Art

[0002] With the acceleration of industrialization, the rapid development of the power industry, especially coal-fired power plants, has led to the generation of a large amount of fly ash. As a solid waste generated in the coal-burning process, fly ash has an annual emission of hundreds of millions of tons. If these fly ashes are not effectively treated and utilized, they will cause serious pollution to the environment, destroy the ecological balance, and also pose a potential threat to human health. Therefore, how to "turn waste into treasure" and realize its resource utilization has become an important issue in solving environmental problems.

[0003] Fly ash is mainly composed of minerals such as mullite and silica, which makes it possible to synthesize porous mullite ceramics. Porous mullite ceramics have broad application prospects in filtration, catalysis, heat exchange and other fields due to their excellent physical and chemical properties, such as high temperature stability, corrosion resistance and good mechanical strength. In recent years, many researchers have begun to explore the method of using fly ash as a raw material to synthesize porous mullite ceramics, in order to achieve high-value utilization of fly ash.

[0004] Gao Yunfeng et al. (Non-metallic Minerals, 2023) used fly ash and bauxite as the main raw materials and starch (introduced in an amount of 20%) as a pore-forming agent to produce mullite porous ceramics. The porosity of the obtained mullite ceramics was about 50%. Wu Lifan et al. (Non-metallic Minerals, 2020) used fly ash and alumina as raw materials and carbon powder (introduced in an amount of 30%) as a pore-forming agent to prepare mullite porous ceramics. The porosity of the obtained mullite porous ceramics was 45.42%. Although the above studies have prepared mullite porous ceramics with higher porosity, there is a large difference in the density of the pore-forming agent and the raw material powder, which can easily lead to uneven distribution of the pore-forming agent and a large discreteness of the pore size distribution; at the same time, the introduction of too much pore-forming agent is also accompanied by large sintering shrinkage during the subsequent sintering process. Large sintering shrinkage may cause deformation and cracking of the sample, and will also increase the subsequent processing cost of the product. How to use fly ash to achieve near-net-size sintering preparation of mullite porous ceramics is of great significance in actual production.

[0005] As we all know, mullite will be accompanied by 7-8% volume expansion during the formation process. Studies have shown (Wang Feng, Ceramics International, 2015) that the volume expansion of the product phase during the sintering process can be used to effectively regulate the microstructure and sintering shrinkage of porous ceramics. Although the introduction of alumina and alumina into fly ash will also be accompanied by volume expansion during the sintering process, the volume expansion is limited. This is because on the one hand, fly ash contains a large amount of mullite phase, which does not contribute to the volume expansion during the sintering process. On the other hand, fly ash contains other impurities that are easy to produce liquid phase during sintering and liquid phase sintering occurs, which leads to a large shrinkage rate (greater than 3%) during the sintering process. Yan Hao et al. (Journal of the Chinese Ceramic Society, 2022) used natural mineral kyanite and alumina powder as raw materials, and combined the gel injection molding process with the pore-forming agent method. By adjusting the solid content of the slurry and combining the volume expansion and sintering shrinkage associated with the mullite formation process, the near-net size preparation of mullite porous ceramics was achieved. However, this preparation method has many influencing factors and the process is relatively complicated.

[0006] Therefore, there is an urgent need to develop a simple and feasible process to realize the resource utilization of fly ash and prepare mullite porous ceramics with low sintering shrinkage and uniform pore size distribution, while overcoming the shortcomings and defects of the existing technology. This can not only effectively utilize the waste fly ash and reduce environmental pollution, but also provide a new material resource with important economic value and environmental significance. Summary of the invention

[0007] The present invention aims to solve the problems existing in the prior art and provides a mullite porous ceramic and a preparation method thereof. The method uses fly ash as a silicon source, an aluminum-containing compound (such as calcined bauxite, alumina, etc.) as an aluminum source, and andalusite as a sintering regulator, and introduces kaolin and a titanium-containing compound as additives, and realizes the near-net-size preparation of mullite porous ceramics through a specific preparation process. The method not only simplifies the production process, but also can effectively control the key performance parameters of the mullite porous ceramics, such as sintering shrinkage, pore size distribution, and mechanical strength.

[0008] Specifically, the preparation method of the present invention comprises the following steps: first, fly ash, aluminum-containing compounds and andalusite are mixed according to the theoretical chemical composition of mullite, wherein the mass fraction of aluminum oxide is 71% to 76%, and the mass fraction of silicon oxide is 29% to 24%. Then, appropriate amounts of kaolin and titanium-containing compounds are added as additives, and mullite porous ceramics are prepared through wet ball milling, suction filtration and drying, granulation and screening, pressing and molding, and segmented sintering.

[0009] The mullite porous ceramic of the present invention has the following characteristic parameters: sintering shrinkage ≤1%, open porosity ≥40%, unimodal pore size distribution, bending strength>50MPa, and good gas flux. The realization of these parameters is due to the precise proportion of raw materials, the introduction of sintering regulators, and the optimization of sintering process in the method of the present invention.

[0010] In the present invention, the introduction of andalusite plays a key role. At high temperature, andalusite reacts with silicon source and aluminum source in fly ash to generate mullite phase. This process is accompanied by volume expansion, which effectively offsets the shrinkage during sintering, thereby realizing the near-net size preparation of mullite porous ceramics. In addition, by controlling the particle size and molding pressure of the raw materials and optimizing the sintering system, the pore size distribution and mechanical strength of the mullite porous ceramics can be further regulated to meet the needs of different application fields.

[0011] Another feature of the present invention is that fly ash is used as the main raw material, which not only realizes the resource utilization of solid waste and reduces environmental pollution, but also reduces the cost of raw materials, with significant economic and environmental benefits. At the same time, by introducing kaolin and titanium-containing compounds as additives, the neck growth between the raw materials can be promoted in the early stage of sintering to form a stable porous structure, further improving the performance of the mullite porous ceramics.

[0012] Specifically, this application adopts the following technical solutions:

[0013] A method for preparing a mullite porous ceramic, characterized in that it comprises the following steps:

[0014] a) using fly ash as a silicon source, aluminum-containing compounds as an aluminum source, and andalusite as a sintering regulator, the ingredients are prepared according to the theoretical chemical composition of mullite, and appropriate amounts of kaolin and titanium-containing compounds are introduced as additives;

[0015] The theoretical chemical composition of mullite refers to a ratio of alumina mass to silicon dioxide mass in the mixture of 71%:29% to 76%:24%.

[0016] b) wet-milling the weighed raw materials, mixing them evenly, and quickly pouring the slurry into a suction filtration device to separate the powder from the liquid medium for ball milling, and then drying them;

[0017] c) adding a binder to the dried powder for granulation and sieving to obtain mixed granulated powder;

[0018] d) placing the granulated powder in a mold, dry pressing or cold isostatic pressing the powder to obtain a green body, and then drying the green body;

[0019] e) placing the dried green body in a sintering furnace and sintering it according to a staged sintering system to obtain a mullite porous ceramic.

[0020] An optional better technical solution: in step a), the particle sizes of fly ash, andalusite and aluminum-containing compound powders in the raw materials are all between 1 and 10 μm.

[0021] An optional better technical solution: in step a), the aluminum-containing compound can be selected from calcined alumina powder and alumina powder, and its alumina content is not less than 70%;

[0022] Optional better technical solution: The titanium-containing compound can be selected from titanium dioxide and titanium tetrachloride.

[0023] An optional better technical solution: the mass ratio of fly ash to andalusite powder is between 2:1 and 4:1, the amount of kaolin introduced is between 0.3% and 0.8%, and the amount of titanium-containing compound introduced is between 0.5% and 1%, wherein the titanium-containing compound is calculated by the mass of titanium oxide.

[0024] An optional better technical solution: in step b), the raw materials are ball-milled for 1 to 6 hours, and the ball-milling speed is 80 to 200 rpm.

[0025] An optional better technical solution: in step c), the binder used is one of polyvinyl alcohol (PVA), polyvinyl butyral (PVB) or sodium carboxymethyl cellulose (CMC).

[0026] An optional better technical solution: In step d), the pressing process used can be dry pressing or cold isostatic pressing; the pressing conditions are: a pressure of 40 to 150 MPa and a holding time of 1 to 4 minutes.

[0027] Optional better technical solution: Step e) the segmented sintering includes a first stage, a second stage and a third stage:

[0028] The first stage is the degreasing stage: the temperature is 450-600℃, the heating rate is 0.5-3℃ / min, and the holding time is 1-4 hours;

[0029] The second stage is the main sintering stage: temperature 1300-1500℃, heating rate 2-5℃ / min, holding time 2-6 hours;

[0030] The third stage is the temperature-controlled cooling stage: the sintering temperature drops to 800±10°C, and the cooling rate is 2-6°C / min.

[0031] An optional and better technical solution: in step e), the first stage of sintering is characterized by the removal of the binder, and the second stage of sintering is characterized by the mutual reaction between the raw materials to generate mullite and form a through porous structure.

[0032] The present application also provides a mullite porous ceramic obtained by the above method.

[0033] As a more optimal technical solution, the mullite porous ceramic has a sintering shrinkage of ≤1%, an open porosity of ≥40%, a unimodal pore size distribution, a bending strength of >50MPa, and good gas flux characteristics.

[0034] An optional better technical solution: the average pore size range of the mullite porous ceramic is 1 to 10 μm.

[0035] Optional better technical solution: The three-point bending strength range of the mullite porous ceramic is >60MPa

[0036] Optional optimal technical solution: The three-point bending strength of the mullite porous ceramic ranges from 60 MPa to 100 MPa.

[0037] Optional better technical solution: The gas flux range of the mullite porous ceramic is 1000m 3 ·m -2 ·h -1 To m 3 ·m -2 ·h -1 .

[0038] As mentioned before, there is a large shrinkage rate when fly ash is sintered with bauxite and alumina. The reason is that liquid phase sintering occurs during the sintering process. After the introduction of andalusite, mullite will be generated by in-situ reaction during the sintering process, accompanied by a certain volume expansion. The volume expansion will offset the subsequent sintering shrinkage, so that the sintering shrinkage of the obtained mullite porous ceramics is effectively suppressed. At the same time, the combination of raw material particle size and the regulation of molding pressure can achieve near-net size sintering molding of mullite porous ceramics. The introduction of a small amount of kaolin and titanium dioxide mainly promotes the neck sintering between large raw material particles in the initial sintering stage, forming a through primary pore channel in the green body.

[0039] The key to achieving the above technical conditions lies in the regulation of the ratio of fly ash to andalusite, raw material particle size, molding pressure and sintering system, so that the volume expansion and sintering shrinkage associated with the formation of mullite in the subsequent sintering process can offset each other.

[0040] In summary, the mullite porous ceramics and the preparation method thereof provided by the present invention successfully prepare mullite porous ceramics with low sintering shrinkage, high open porosity, uniform pore size distribution and excellent mechanical strength through precise raw material ratio, sintering control and process optimization.

[0041] This mullite porous ceramic can not only effectively utilize waste fly ash and reduce environmental pressure, but also, due to its excellent performance, can be widely used in filtration, catalysis, heat exchange, biomedicine and environmental protection and other fields. It has important practical value and broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a microstructure diagram of the mullite porous ceramic in Example 1.

[0043] Figure 2 This is the pore size distribution diagram of the mullite porous ceramic in Example 1.

[0044] Figure 3 This is a microstructure diagram of the mullite porous ceramic in Example 2.

[0045] Figure 4 This is the pore size distribution diagram of the mullite porous ceramic in Example 2. DETAILED DESCRIPTION

[0046] Embodiment 1:

[0047] A method for preparing mullite porous ceramics, the specific steps are as follows:

[0048] 1. Raw material preparation: fly ash with a particle size (D50) of 6 μm, andalusite powder with a particle size of 2.5 μm, and calcined alumina powder with a particle size of 10 μm are selected as raw materials. The aluminum oxide content of fly ash is 29.40%, the silicon oxide content is 58.17%, and the impurity content is 12.43%; the aluminum oxide content of andalusite is 58.9%, the silicon oxide content is 38.5%, and the impurity content is 2.6%; the aluminum oxide content of calcined alumina is 79.41%, the silicon oxide content is 9.28%, and the impurity content is 11.31%.

[0049] 2. Batching and mixing: Batching is carried out according to the mass ratio of the theoretical chemical composition of mullite (Al2O3:SiO2=71.79:28.21). The mass ratio of fly ash to andalusite is set to 4:1, specifically, the mass of andalusite is 10.86g, the mass of fly ash is 43.45g, and the mass of calcined alumina is 100g. In addition, kaolin and 0.5% titanium oxide are weighed as additives relative to 0.5% of the total mass of fly ash, andalusite and calcined alumina. All raw materials are placed in a ball mill and wet-milled at a rate of 120r / min for 2 hours to ensure uniform mixing.

[0050] 3. Filtration and drying: The milled slurry is quickly poured into the filtration device for filtration to remove the water. Subsequently, the filtered powder is dried to facilitate the subsequent granulation and molding process.

[0051] 4. Granulation and molding: The dried powder is mixed with a polyvinyl alcohol aqueous solution of 3% relative to the mass of the mixed powder, and granulated to obtain granulated powder suitable for pressing. The obtained granulated powder is sieved through an 80-mesh nylon sieve, and then placed in a steel mold and pressed at a pressure of 80 MPa for 2 minutes to form a molded blank. After that, the blank is placed in an oven at 100°C for drying for 10 hours.

[0052] 5. Debinding and sintering: Place the dried green blank in a muffle furnace for debinding and sintering. During the debinding stage, heat to 120°C at a rate of 4°C / min and keep warm for 1 hour, then heat to 350°C at a rate of 1.5°C / min and keep warm for 1 hour, and finally heat to 600°C at a rate of 2°C / min and keep warm for 2 hours. During the sintering stage, heat to 1000°C at a rate of 5°C / min and keep warm for 2 hours, then heat to 1400°C at a rate of 2°C / min and keep warm for 2 hours. After sintering, cool to 600°C at a rate of 4°C / min, and then cool naturally to room temperature.

[0053] Through the above preparation process, the sintering shrinkage of the obtained mullite porous ceramic is 0.2%, showing a relatively uniform microstructure. The pore size distribution shows a single peak distribution, and the average pore size is 7.5μm. In addition, the three-point bending strength of the mullite porous ceramic reaches 61MPa, and the gas flux at a pressure of 0.1MPa is 2072m 3 ·m -2 ·h -1 , indicating that the material has good mechanical properties and air permeability.

[0054] Example 2

[0055] This embodiment provides another method for preparing mullite porous ceramics, and the specific steps are as follows:

[0056] 1. Raw material preparation: andalusite powder with a particle size of 6μm, fly ash with a particle size of 8μm, and alumina powder with a particle size of 4μm are used as raw materials. The alumina content of fly ash is 29.40%, the silicon oxide content is 58.17%, and the impurity content is 12.43%; the alumina content of andalusite is 58.9%, the silicon oxide content is 38.5%, and the impurity content is 2.6%.

[0057] 2. Batching and mixing: Batching is carried out according to the mass ratio of the theoretical chemical composition of mullite (Al2O3:SiO2=74:26). The mass ratio of fly ash to andalusite is set to 2.5:1, specifically, the mass of andalusite is 25.5g, the mass of fly ash is 63.8g, and the mass of alumina is 100g. In addition, kaolin and 1% titanium oxide are weighed as additives relative to 0.3% of the total mass of fly ash, andalusite and alumina. Put all the raw materials into a ball mill and wet-mill them at a rate of 150r / min for 2 hours to ensure uniform mixing.

[0058] 3. Filtration and drying: The milled slurry is quickly poured into the filtration device for filtration to remove the water. Subsequently, the filtered powder is dried to facilitate the subsequent granulation and molding process.

[0059] 4. Granulation and molding: The dried powder is mixed with a polyvinyl alcohol aqueous solution at a mass of 2% relative to the mass of the mixed powder, and granulated to obtain granulated powder suitable for pressing. The obtained granulated powder is sieved through a 100-mesh nylon sieve, and then placed in a steel mold and pressed at a pressure of 100 MPa for 4 minutes to form a molded blank. After that, the blank is placed in an oven at 120°C for drying for 6 hours.

[0060] 5. Debinding and sintering: Place the dried green blank in a muffle furnace for debinding and sintering. During the debinding stage, heat to 100°C at a rate of 4°C / min and keep warm for 1.5 hours, then heat to 600°C at a rate of 2°C / min and keep warm for 2 hours. During the sintering stage, heat to 1100°C at a rate of 4°C / min and keep warm for 1 hour, then heat to 1450°C at a rate of 2°C / min and keep warm for 2 hours. After sintering, cool to 800°C at a rate of 5°C / min, and then cool naturally to room temperature.

[0061] Through the above preparation process, the sintering shrinkage of the obtained mullite porous ceramic is 0.5%, and the microstructure is as follows Figure 3 As shown in the figure, the pore size distribution presents a unimodal distribution with an average pore size of 5.1 μm. In addition, the three-point bending strength of the mullite porous ceramic reaches 73 MPa, and the gas flux at a pressure of 0.1 MPa is 1876 m 3 ·m -2 ·h -1 , indicating that the material has good mechanical properties and air permeability.

[0062] Compared with Example 1, the performance of the mullite porous ceramic is further improved by increasing the content of alumina in the raw materials, adjusting the proportion of additives and optimizing the sintering temperature in Example 2. This improvement shows that the performance of the mullite porous ceramic can be customized according to different application requirements by finely controlling the raw material ratio and sintering process.

[0063] Example 3

[0064] This embodiment provides another method for preparing mullite porous ceramics, and the specific steps are as follows:

[0065] 1. Raw material preparation: fly ash with a particle size (D50) of 5μm, andalusite powder with a particle size of 3μm, and calcined alumina powder with a particle size of 5μm are selected as raw materials. The content of aluminum oxide in fly ash is 30%, the content of silicon oxide is 55%, and the content of impurities is 15%; the content of aluminum oxide in andalusite is 60%, the content of silicon oxide is 37%, and the content of impurities is 3%; the content of aluminum oxide in calcined alumina is 80%, the content of silicon oxide is 10%, and the content of impurities is 10%.

[0066] 2. Batching and mixing: Batching is carried out according to the mass ratio of the theoretical chemical composition of mullite (Al2O3:SiO2=72:28). The mass ratio of fly ash to andalusite is set to 3:1, specifically, the mass of andalusite is 15g, the mass of fly ash is 45g, and the mass of calcined alumina is 90g. In addition, kaolin and 0.6% titanium oxide are weighed as additives relative to 0.4% of the total mass of fly ash, andalusite and calcined alumina. Put all the raw materials into a ball mill and perform wet ball milling at a rate of 130r / min for 2.5 hours to ensure uniform mixing.

[0067] 3. Filtration and drying: The milled slurry is quickly poured into the filtration device for filtration to remove the water. Subsequently, the filtered powder is dried to facilitate the subsequent granulation and molding process.

[0068] 4. Granulation and molding: The dried powder is mixed with a polyvinyl alcohol aqueous solution of 2.5% relative to the mass of the mixed powder, and granulated to obtain granulated powder suitable for pressing. The obtained granulated powder is sieved through a 90-mesh nylon sieve, and then placed in a steel mold and pressed at a pressure of 85 MPa for 3 minutes to form a molded blank. After that, the blank is placed in an oven at 105°C for drying for 8 hours.

[0069] 5. Debinding and sintering: Place the dried green blank in a muffle furnace for debinding and sintering. During the debinding stage, heat to 150°C at a rate of 3°C / min and keep warm for 1.5 hours, then heat to 500°C at a rate of 2°C / min and keep warm for 2 hours. During the sintering stage, heat to 1050°C at a rate of 4°C / min and keep warm for 1.5 hours, then heat to 1380°C at a rate of 3°C / min and keep warm for 2 hours. After sintering, cool to 700°C at a rate of 5°C / min, and then cool naturally to room temperature.

[0070] Through the above preparation process, the sintering shrinkage of the obtained mullite porous ceramic is 0.3%, and the microstructure shows a relatively uniform pore distribution. The pore size distribution shows a single peak distribution, and the average pore size is 6.5μm. In addition, the three-point bending strength of the mullite porous ceramic reaches 65MPa, and the gas flux at a pressure of 0.1MPa is 2150m 3 ·m -2 ·h -1 , indicating that the material has good mechanical properties and air permeability.

[0071] Compared with the first two embodiments, the performance of the mullite porous ceramic is further improved in Embodiment 3 by adjusting the particle size of the raw material, increasing the content of alumina in the raw material, adjusting the proportion of additives, and optimizing the sintering temperature and holding time.

[0072] Example 4

[0073] This embodiment provides another method for preparing mullite porous ceramics, and the specific steps are as follows:

[0074] 1. Raw material preparation: fly ash with a particle size (D50) of 4.5 μm, andalusite powder with a particle size of 3.5 μm, and calcined alumina powder with a particle size of 6 μm are selected as raw materials. The content of aluminum oxide in fly ash is 31%, the content of silicon oxide is 54%, and the content of impurities is 15%; the content of aluminum oxide in andalusite is 59%, the content of silicon oxide is 36%, and the content of impurities is 5%; the content of aluminum oxide in calcined alumina is 81%, the content of silicon oxide is 9%, and the content of impurities is 10%.

[0075] 2. Batching and mixing: Batching is carried out according to the mass ratio of the theoretical chemical composition of mullite (Al2O3:SiO2=73:27). The mass ratio of fly ash to andalusite is set to 3.5:1, specifically, the mass of andalusite is 20g, the mass of fly ash is 70g, and the mass of calcined alumina is 80g. In addition, diatomaceous earth and 0.7% zirconium oxide are weighed as additives relative to 0.4% of the total mass of fly ash, andalusite and calcined alumina. All raw materials are placed in a ball mill and wet-milled at a rate of 140r / min for 3 hours to ensure uniform mixing.

[0076] 3. Filtration and drying: The milled slurry is quickly poured into the filtration device for filtration to remove the water. Subsequently, the filtered powder is dried to facilitate the subsequent granulation and molding process.

[0077] 4. Granulation and molding: The dried powder is mixed with a polyvinyl alcohol aqueous solution of 3% relative to the mass of the mixed powder, and granulated to obtain granulated powder suitable for pressing. The obtained granulated powder is sieved through an 80-mesh nylon sieve, and then placed in a steel mold and pressed at a pressure of 90 MPa for 5 minutes to form a molded blank. After that, the blank is placed in an oven at 110°C for drying for 12 hours.

[0078] 5. Debinding and sintering: Place the dried green blank in a muffle furnace for debinding and sintering in a nitrogen atmosphere. During the debinding stage, heat to 200°C at a rate of 3°C / min and keep warm for 2 hours, then heat to 550°C at a rate of 2°C / min and keep warm for 2.5 hours. During the sintering stage, heat to 1150°C at a rate of 5°C / min and keep warm for 2 hours, then heat to 1420°C at a rate of 3°C / min and keep warm for 3 hours. After sintering, cool to room temperature at a rate of 6°C / min.

[0079] Through the above preparation process, the sintering shrinkage of the obtained mullite porous ceramic is 0.4%, the microstructure shows a relatively uniform pore distribution, the pore size distribution presents a single peak distribution, and the average pore size is 4.8μm. In addition, the three-point bending strength of the mullite porous ceramic reaches 70MPa, and the gas flux at a pressure of 0.1MPa is 2300m 3 ·m -2 ·h -1 , indicating that the material has good mechanical properties and air permeability.

[0080] In this embodiment, a mullite porous ceramic with higher thermal stability and chemical stability was successfully prepared by introducing a nitrogen atmosphere during the sintering process. This mullite porous ceramic not only has low sintering shrinkage, uniform pore size distribution and high bending strength, but also exhibits good gas flux performance, and is suitable for filtration, catalysis, heat exchange and other fields that require higher thermal stability and chemical stability.

[0081] Compared with the previous embodiments, the performance of the mullite porous ceramic is further improved in Embodiment 4 by adjusting the particle size of the raw material, increasing the content of alumina in the raw material, adjusting the proportion of additives, optimizing the sintering temperature and holding time, and specially introducing nitrogen atmosphere sintering.

[0082] Example 5

[0083] This embodiment provides another method for preparing mullite porous ceramics, and the specific steps are as follows:

[0084] 1. Raw material preparation: fly ash with a particle size (D50) of 4μm, andalusite powder with a particle size of 2μm, and synthetic mullite powder with a particle size of 5μm are selected as raw materials. The aluminum oxide content of fly ash is 32%, the silicon oxide content is 53%, and the impurity content is 15%; the aluminum oxide content of andalusite is 61%, the silicon oxide content is 35%, and the impurity content is 4%; the aluminum oxide content of synthetic mullite is 85%, the silicon oxide content is 13%, and the impurity content is 2%.

[0085] 2. Batching and mixing: Batching is carried out according to the mass ratio of the theoretical chemical composition of mullite (Al2O3:SiO2=71:29). The mass ratio of fly ash, andalusite and synthetic mullite is set to 2:1:2, specifically, the mass of andalusite is 20g, the mass of fly ash is 40g, and the mass of synthetic mullite is 40g. In addition, calcium carbonate and 1% diatomaceous earth are weighed as additives relative to 0.5% of the total mass of fly ash, andalusite and synthetic mullite. All raw materials are placed in a ball mill and wet-milled at a rate of 120r / min for 4 hours to ensure uniform mixing.

[0086] 3. Filtration and drying: The milled slurry is quickly poured into the filtration device for filtration to remove the water. Subsequently, the filtered powder is dried to facilitate the subsequent granulation and molding process.

[0087] 4. Granulation and molding: The dried powder is mixed with a polyvinyl alcohol aqueous solution of 2% relative to the mass of the mixed powder, and granulated to obtain granulated powder suitable for pressing. The obtained granulated powder is sieved through a 100-mesh nylon sieve, and then placed in a steel mold and pressed at a pressure of 95 MPa for 4 minutes to form a molded blank. After that, the blank is placed in an oven at 115°C for drying for 10 hours.

[0088] 5. Microwave-assisted sintering: Place the dried green blank in a microwave oven and perform sintering under the assistance of microwaves. During the sintering stage, first heat up to 600°C at a rate of 5°C / min and keep it at that temperature for 1 hour to complete the degreasing process. Then, heat up to 1400°C at a rate of 10°C / min and keep it at that temperature for 2 hours to complete the sintering process. After sintering, turn off the microwave source and let the sample cool naturally to room temperature in the furnace.

[0089] Through the above preparation process, the sintering shrinkage of the obtained mullite porous ceramic is 0.2%, the microstructure shows a very uniform pore distribution, the pore size distribution shows a single peak distribution, and the average pore size is 3.5μm. In addition, the three-point bending strength of the mullite porous ceramic reaches 75MPa, and the gas flux at a pressure of 0.1MPa is 2500m 3 ·m -2 ·h -1 .

[0090] In this embodiment, by adopting microwave assisted sintering technology, the sintering time is successfully shortened, and the uniformity and overall performance of the mullite porous ceramic are improved. Microwave sintering has the advantages of fast heating speed, high energy utilization rate, and uniform temperature field distribution, which helps to improve the sintering efficiency and product quality of mullite porous ceramics.

[0091] Compared with the previous embodiments, in Embodiment 5, the performance of the mullite porous ceramic is further improved by introducing synthetic mullite powder and special additives and adopting microwave assisted sintering technology.

[0092] The examples show the preparation method and optimization process of mullite porous ceramics through five specific examples, and each example reflects a significant improvement in the performance of mullite porous ceramics. By finely controlling the raw material ratio, the selection and proportion of additives, the sintering process and conditions, the multi-faceted optimization of the performance of mullite porous ceramics is achieved, including but not limited to improving mechanical strength, improving pore structure, enhancing thermal stability and chemical stability, and shortening sintering time. These improvements not only improve the air permeability and filtration efficiency of mullite porous ceramics, but also enhance its application potential in high temperature and corrosive environments, showing excellent comprehensive performance.

[0093] The mullite porous ceramic described in this application is a high-performance refractory material, which is not only suitable for filtration, catalysis, heat exchange and other fields under high temperature, high pressure and corrosive environment, but also can be widely used in petrochemical, metallurgy, environmental protection, energy and other industries.

[0094] In practical applications, this mullite porous ceramic can be customized to meet specific application conditions by adjusting parameters such as pore size, porosity and mechanical strength according to the specific needs of different industrial fields.

Claims

1. A method for preparing a mullite porous ceramic, characterized in that: The following steps are involved: a) using fly ash as a silicon source, aluminum-containing compounds as an aluminum source, and andalusite as a sintering regulator, the ingredients are prepared according to the theoretical chemical composition of mullite, and appropriate amounts of kaolin and titanium-containing compounds are introduced as additives; The theoretical chemical composition of mullite refers to a ratio of alumina mass to silicon dioxide mass in the mixture of 71%:29% to 76%:24%. b) wet-milling the weighed raw materials, mixing them evenly, and quickly pouring the slurry into a suction filtration device to separate the powder from the liquid medium for ball milling, and then drying them; c) adding a binder to the dried powder for granulation and sieving to obtain mixed granulated powder; d) placing the granulated powder in a mold, dry pressing or cold isostatic pressing the powder to obtain a green body, and then drying the green body; e) placing the dried green body in a sintering furnace and sintering it according to a staged sintering system to obtain a mullite porous ceramic.

2. The preparation method according to claim 1, characterized in that: In step a), the particle sizes of fly ash, andalusite and aluminum-containing compound powders in the raw materials are all between 1 and 10 μm.

3. The preparation method according to claim 1, characterized in that: In step a), The aluminum-containing compound may be selected from calcined alumina powder and alumina powder, and its alumina content is not less than 70%; The titanium-containing compound may be selected from titanium dioxide and titanium tetrachloride.

4. The preparation method according to claim 1, characterized in that: The mass ratio of fly ash to andalusite powder is between 2:1 and 4:1, the amount of kaolin introduced is between 0.3% and 0.8%, and the amount of titanium-containing compound introduced is between 0.5% and 1%, wherein the titanium-containing compound is calculated by the mass of titanium oxide.

5. The preparation method according to claim 1, characterized in that: In step b), the raw materials are ball-milled for 1 to 6 hours, and the ball-milling speed is 80 to 200 rpm.

6. The preparation method according to claim 1, characterized in that: In step c), the binder used is one of polyvinyl alcohol (PVA), polyvinyl butyral (PVB) or sodium carboxymethyl cellulose (CMC).

7. The preparation method according to claim 1, characterized in that: In step d), the pressing process used can be dry pressing or cold isostatic pressing; the pressing conditions are: pressure of 40 to 150 MPa, and holding time of 1 to 4 minutes.

8. The preparation method according to claim 1, characterized in that: The staged sintering in step e) includes a first stage, a second stage and a third stage: The first stage is the degreasing stage: the temperature is 450-600℃, the heating rate is 0.5-3℃ / min, and the holding time is 1-4 hours; The second stage is the main sintering stage: temperature 1300-1500℃, heating rate 2-5℃ / min, holding time 2-6 hours; The third stage is the temperature-controlled cooling stage: the sintering temperature drops to 800±10°C, and the cooling rate is 2-6°C / min.

9. The preparation method according to claim 1, characterized in that: In step e), the first stage of sintering is characterized by the removal of the binder, and the second stage of sintering is characterized by the mutual reaction between the raw materials to generate mullite and form a through porous structure.

10. A mullite porous ceramic, characterized in that: The mullite porous ceramic prepared by the preparation method according to any one of claims 1 to 9 has a sintering shrinkage of ≤1%, an open porosity of ≥40%, a unimodal pore size distribution, a bending strength of >50MPa, and good gas flux characteristics.

Citation Information

Cited By

  • Method for preparing mullite-based porous ceramic material from biochar and coal co-gasification fly ash

    CN120647423A